Deposit‐feeder diets in the Bering Sea: potential effects of climatic loss of sea ice‐related microalgal blooms. Issue 6 (1st September 2014) - North, Christopher A.; Lovvorn, James R.; Kolts, Jason M.; Brooks, Marjorie L.; Cooper, Lee W.; Grebmeier, Jacqueline M.
Abstract : Climate warming in seasonally ice‐covered seas is expected to reduce the extent and duration of annual sea ice. Resulting changes in sea ice related blooms of ice algae or phytoplankton may in turn alter the timing, magnitude, or quality of organic matter inputs to the sea floor. If benthic taxa rely differently on direct consumption of settling fresh microalgae for growth and reproduction, altered blooms may lead to reorganization of deposit‐feeding assemblages. To assess the potential for such changes, we examined the diets of five abundant deposit‐feeders (three infaunal bivalves, a polychaete, and a brittle star) with different feeding modes over the course of the spring bloom in May–June 2007 in the north‐central Bering Sea (30–90 m depth). Short‐term data from gut contents reflected feeding modes, with the bivalves Macoma calcarea, Ennucula tenuis, and Nuculana radiata, and the brittle star Ophiura sarsi, responding more quickly to deposition of fresh algae than did the head‐down polychaete Pectinaria hyperborea . Fatty acid biomarkers also indicated rapid ingestion of settling algae by the bivalves (especially Macoma ) and the brittle star, while Pectinaria continued to ingest mainly bacteria. Fatty acid biomarkers did not indicate any unique dietary importance of ice algae released from melting ice. Longer‐term inference from stable isotopes suggested that fresh microalgae contributed little to overall carbon assimilated by any of these species. Instead, deposit‐feeders appeared to select a consistent fraction from the pool of sediment organic matter, probably heterotrophic microbes, microbial products, and reworked phytodetritus that form a longer‐term sediment "food bank." Redistribution of settled organic matter via scouring and accumulation by currents, as well as the multi‐year life spans of macroinvertebrates, may further overwhelm effects of short‐term variations in the timing, magnitude, and dispersion of blooms in the water column. More diet data are needed from midsummer to account for any lag in assimilation of fresh microalgae at these cold temperatures. Nevertheless, our results suggest that if annual sea ice cover is reduced, increased production of phytoplankton during longer ice‐free periods could replace inputs of ice‐associated microalgae to the sediment food bank used by deposit‐feeders.